LEADERSHIP DAN ORGANIZATIONAL CULTURE: PENGARUHNYA TERHADAP LEARNING ORGANIZATION DAN EMPLOYEE'S JOB SATISFACTION - Netania Emilisa (Universitas Trisakti, 2012)
The purpose of this study is to investigate the relationship among Leadership, Organizational culture, the operation of Learning organization and Employee's job satisfaction. The result obtained from 224 respondents which are selected using purposive sampling and analyzing using Structural Equation Modeling from AMOS. This research indicate that the various operation extents of Learning organization have significant difference under the dimensions of Leadership, Organizational culture and the operation of Learning organization. Leadership has significantly and positively influence Learning organization, Organizational culture is not signifantly effect on Leadership, both Leadership and Learning organization have a significantly positive effect on Employee's job satisfaction. One more finding is Organizational culture is not significantly has an effect to employee's job satisfaction.Keywords: Leadership, Organizational culture, Learning organization, Job satisfaction